Pasting properties, texture profile and stress-relaxation behavior of wheat starch/dietary fiber systems - Yildiz, Onder; Yurt, Bayram; Basturk, Ayhan; Toker, Omer Said; Yilmaz, Mustafa Tahsin; Karaman, Safa; Daglioglu, Orhan (ELSEVIER SCIENCE BV, 2013)
The effect of dietary fiber type (oat, pea, lemon and apple) and concentration (0, 2.5, 5, 10, 15 and 20% w/w) on theological properties of wheat starch/fiber systems was evaluated based on their pasting properties; texture profile and stress-relaxation behavior. Peak, trough, breakdown, final and setback viscosity increased; however, peak time and pasting temperature decreased as fiber concentration increased. The lemon fiber was the most effective in increasing the pasting viscosity parameters, and in decreasing pasting temperature, followed by apple, pea and oat fibers. The effect of fiber concentration was successfully described by power-law and exponential type models; however, estimating the performance of exponential model was generally better. Regarding texture profile, an increase in fiber concentration linearly decreased hardness, adhesiveness, gumminess and chewiness values of the starch/lemon fiber and starch/apple fiber gels. Maxwell, Nussinovitch and Peleg models were used to evaluate the stress relaxation data. Maxwell and Peleg models were the best in representing the stress relaxation behavior; however, Nussinovitch model was also valid. Fiber addition changed the stress relaxation properties, which was remarkable depending on fiber concentration. Fiber addition increased the elasticity of wheat starch gel. To summarize, fiber addition provided an increase in resistance of wheat starch gel to deformation, as revealed by the RVA, TPA and stress relaxation tests. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Wheat starch; Dietary fiber; Pasting properties; Texture profile; Stress relaxation; Mechanical simulation models; RHEOLOGICAL PROPERTIES; NONSTARCH POLYSACCHARIDES; VISCOELASTIC PROPERTIES; XANTHAN GUM; STARCH; KERNELS; FLOUR; FOODS; AMYLOPECTIN; Food Science & Technology